Measuring the Extent and Implications of Director Interlocking in the Pre-war Japanese Banking Industry - Tetsuji Okazaki; Kazuki Yokoyama (Asian Development Bank Institute (ADBI), 2002)
As a result of the Asian financial crisis of 1997, the issue of corporate governance has attracted the attention of researchers as well as policy authorities. Much of the literature on the Asian crisis focuses specifically on the exploitation of minority shareholders by core members of family-based companies (Claessens et al. (1998); Lang (2001)). We argue that family-based companies do not always exploit minority shareholders. Okazaki (1999) and Okazaki (2001) indicate that the companies affiliated to the major zaibatsu in pre-war Japan basically outperformed other companies in terms of ROE, using panel data of 1935 companies from 1922 to 1936. According to the book and paper, this was basically due to monitoring by the holding company through dispatching directors, checking financial records and so on. However, the existence of major zaibatsu such as Mitsui and Mitsubishi was only one aspect of the pre-war Japanese corporate system. In addition to the major zaibatsu, many small and mediumsized family-based corporate groups existed.
hdl:11540/4145
Keywords: 330; Bank; Eigentümerstruktur; Vorstand; Kredit; Lieferantenmanagement; Japan